Applicability of Hybrid Built-Up Wide Flange Steel Beams - Ju, Hyunjin; Lee, Se-Jung; Choi, Sung-Mo; Kim, Jong; Lee, Deuckhang (MDPI, 2020)
To accommodate growing demands on either heavy steel structures or unique buildings with irregular configurations, built-up wide-flange steel (BWS) beams are being popularly used in modern steel construction. In current fabrication practices of BWS members, high-performance steels produced in steelmaking factories under the thermo-mechanical control process (TMCP) are typically utilized to achieve proper welding performances. However, since its basic unit price is quite higher than typical hot-rolled steel materials, this study introduced a hybrid BWS section for cost saving with no performance degradation, where high-performance TMCP steel was used in flanges, and conventional hot-rolled steel was adopted in web plate. To verify the tensile performances of a hybrid BWS section with non-uniform properties, split T tension and Charpy impact tests were conducted, and flexural tests were also carried out on hybrid and homogeneous BWS beam members. On this basis, it was confirmed that the structural performance of the hybrid BWS member is comparable with that of the conventional one with a uniform section property.
Keywords: Research Subject Categories::TECHNOLOGY; built-up steel member; different steel type; welding; structural experiment; finite element method